2016
DOI: 10.1038/srep36350
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics, population characterization and mycotoxins accumulation of Fusarium graminearum in Eastern China

Abstract: Trichothecene genotype composition, mycotoxin production, genetic diversity, and population structure were analyzed, using 185 Fusarium strains collected from wheat (Triticum aestivum L.) throughout the Jiangsu province during 1976, 1983, 1998, 2006, and 2014. The results showed that 3-acetyldeoxynivalenol (3ADON) was consistently the predominant type in this region over 40 years, and the nivalenol (NIV) type has emerged since 1998. Long-term rotation of wheat and rice (Oryza sativa L.), rather than fungicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…In Japan, F. graminearum is most prevalent in wheat fields in the northern parts of the country, which feature low temperatures, while F. asiaticum is the most abundant species in the southern region, which features higher temperatures (Suga et al 2008). Similar results with respect to geography have been obtained in China, where approximately 76% of isolates obtained from wheat in the northeast parts of the country were of the F. graminearum species, while 97% of isolates collected from the southern region were of the F. asiaticum species (Zhang et al 2010;Qiu et al 2016). Surveys undertaken in Argentina, Brazil, and Uruguay have also shown F. graminearum to be the major causative pathogen (Ramirez et al 2007;Reynoso et al 2011;Castañares et al 2014;Yerkovich et al 2020).…”
Section: Fusarium Species Causing Fhb In Wheat and Barleysupporting
confidence: 65%
See 1 more Smart Citation
“…In Japan, F. graminearum is most prevalent in wheat fields in the northern parts of the country, which feature low temperatures, while F. asiaticum is the most abundant species in the southern region, which features higher temperatures (Suga et al 2008). Similar results with respect to geography have been obtained in China, where approximately 76% of isolates obtained from wheat in the northeast parts of the country were of the F. graminearum species, while 97% of isolates collected from the southern region were of the F. asiaticum species (Zhang et al 2010;Qiu et al 2016). Surveys undertaken in Argentina, Brazil, and Uruguay have also shown F. graminearum to be the major causative pathogen (Ramirez et al 2007;Reynoso et al 2011;Castañares et al 2014;Yerkovich et al 2020).…”
Section: Fusarium Species Causing Fhb In Wheat and Barleysupporting
confidence: 65%
“…Additionally, the 3ADON isolates were more aggressive and showed higher levels of fungicide resistance. In China, VNTR marker analysis of 185 Fusarium isolates collected within a 28-year period resulted in a strong correlation between highgenetic diversity and mycotoxin production (Qiu et al 2016). These results suggest natural selection as a dominant force in the introduction of more toxigenic pathogens into a region.…”
Section: Trichothecene Mycotoxin Chemotypes and The Population Genetic Structures Of Fusarium Species Causing Fhb In Wheat And Barleymentioning
confidence: 93%
“…The F. graminearum VNTR markers have been widely used in F. graminearum population genetic analysis [ 7 , 9 , 24 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the current study, a high level of polymorphism was detected as indicated by the relatively high Shannon Index values across the geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The population structure and genetic variation in FHB pathogens have been studied in detail in Jiangsu Province, which has a long history of rice growing and a large rice-growing area that covers 30 million acres. The F. asiaticum strain that produced 3ADON has always dominated [60,61], and no similar evidence of temporal trends in the North American wheat population or Chinese barley population has been found [62,63,64,65,66]. Extensive wheat-rice rotation is critical for F. asiaticum overwintering, and perithecium production typically favors rice straw under warmer conditions.…”
Section: Toxin-producing Fusarium Strainsmentioning
confidence: 99%